2016
DOI: 10.1111/jnp.12098
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery in spinal cord injured people is modulated by somatotopic coding, perspective taking, and post‐lesional chronic pain

Abstract: Motor imagery (MI) allows one to mentally represent an action without necessarily performing it. Importantly, however, MI is profoundly influenced by the ability to actually execute actions, as demonstrated by the impairment of this ability as a consequence of lesions in motor cortices, limb amputations, movement limiting chronic pain, and spinal cord injury. Understanding MI and its deficits in patients with motor limitations is fundamentally important as development of some brain-computer interfaces and dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 71 publications
4
60
0
Order By: Relevance
“…Conversely, people affected by PCL who regularly perform sport become more expert than healthy people and PCL patients who do not practise sport when discriminating upper body parts 36 . Moreover, somato-topographic changes concerning the sense of ownership and motor imagery have been demonstrated in people with SCI 32 34 . Thus, somatic afferences and motor efferences play a crucial role in building, maintaining and adapting the representations of one’s own body and in all the high cognitive functions which are connected in some way to body perception and action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, people affected by PCL who regularly perform sport become more expert than healthy people and PCL patients who do not practise sport when discriminating upper body parts 36 . Moreover, somato-topographic changes concerning the sense of ownership and motor imagery have been demonstrated in people with SCI 32 34 . Thus, somatic afferences and motor efferences play a crucial role in building, maintaining and adapting the representations of one’s own body and in all the high cognitive functions which are connected in some way to body perception and action.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that SCI induces brain plasticity 27 28 29 30 31 with changes in bodily representations 32 33 , in motor imagery 34 , in mental rotation of body parts 35 and in the visual discrimination of body actions and forms 36 . Interestingly, these changes seem to follow somato-topic rules 32 34 35 36 .…”
mentioning
confidence: 99%
“…Moreover, Kalicinski, Kempe (28) recommended, that the task complexity should be taken into account when MI ability is assessed, as complexity of a task might affect MI performance (a more di cult task leads to reduced MI ability score) (50).…”
Section: Perspective Preferencementioning
confidence: 99%
“…Several authors described that the use of both MI perspectives could be bene cial in different ways depending on the motor task to be imagined and what aspect of the performance should be enhanced (13,50). White and Hardy (20) described that imagery from an internal perspective improved motor performance accuracy, thus imagery from an external perspective improved speed.…”
Section: Perspective Preferencementioning
confidence: 99%
See 1 more Smart Citation